Calving Problems and Early Viability of the Calf 1979
DOI: 10.1007/978-94-009-9315-0_21
|View full text |Cite
|
Sign up to set email alerts
|

Use of Prostaglandins for Induction of Parturition in the Cow

Abstract: In the cow. the corpus luteum is considered to be the main SOl~ce

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…THORNBURN et al (1977) found that oestradiol-17P plays an important role in the initiation of parturition and the delivery of the placenta. According to GRONEBORG-PEDERSEN (1969), parturition can be induced by administration of oestradiol benzoate, whereas Bosc (1977) could not confirm this finding. Elevated concentrations of unconjugated oestrogens are a prerequisite for normal (CALLAHAN et al, 1969) or glucocorticoid (MOSTL et al, 1985 but not for prostaglandininduced parturition ( KAKER et al, 1984).…”
Section: Introductionmentioning
confidence: 94%
“…THORNBURN et al (1977) found that oestradiol-17P plays an important role in the initiation of parturition and the delivery of the placenta. According to GRONEBORG-PEDERSEN (1969), parturition can be induced by administration of oestradiol benzoate, whereas Bosc (1977) could not confirm this finding. Elevated concentrations of unconjugated oestrogens are a prerequisite for normal (CALLAHAN et al, 1969) or glucocorticoid (MOSTL et al, 1985 but not for prostaglandininduced parturition ( KAKER et al, 1984).…”
Section: Introductionmentioning
confidence: 94%